Strategies to improve sexual health in women with urinary incontinence: A scoping review - Zoleikha Askarloo; Shadab Shahali; Fazlollah Ahmadi; Ali Montazeri (PLoS ONE, 2026)
Background Urinary incontinence (UI), affecting 3%–55% of women worldwide, significantly impairs sexual health and quality of life. Despite its prevalence, interventions targeting sexual dysfunction in this population are understudied. This scoping review synthesizes evidence on strategies to improve sexual health in women with UI, aiming to guide clinical practice and future research. Methods Adhering to Arksey and O’Malley’s scoping review framework, we systematically searched PubMed, Scopus, Web of Science, and gray literature (2015–2025) for studies on interventions addressing sexual health in women with UI. Two reviewers independently screened and extracted data, synthesizing findings narratively into four categories: non-surgical interventions, surgical interventions, comparative effectiveness, and partner sexual function. Results The included 31 studies evaluated a broad range of interventions, including pelvic floor muscle training, behavioral therapies, pharmacological treatments, and surgical procedures. Reported effects on sexual function were inconsistent and varied across studies, depending on intervention type, study design, baseline sexual function status, and measurement tools. While some studies reported improvements in specific domains of sexual function following certain interventions, others reported no significant change or mixed outcomes. Evidence regarding partner-related sexual outcomes was limited and based on a small number of studies with modest sample sizes. Conclusion This scoping review demonstrates that multiple interventions have been explored for their potential impact on sexual function in women with urinary incontinence; however, the available evidence is heterogeneous and largely descriptive. Due to variability in populations, interventions, and outcome assessment, no definitive conclusions regarding effectiveness or comparative benefit can be drawn. Future research using standardized sexual function measures and clearly defined populations is needed to better inform clinical practice and guideline development.